Decreased Susceptibility to Azithromycin in Clinical Shigella Isolates Associated with HIV and Sexually Transmitted Bacterial Diseases, Minnesota, USA, 2012–2015 - Eikmeier, Dana (Emerg Infect Dis, 2020)
Shigellosis outbreaks caused by Shigella with decreased susceptibility to azithromycin (DSA-Shigella) among men who have sex with men (MSM) have been reported worldwide. We describe sexual health indicators and antimicrobial drug resistance for shigellosis cases in Minnesota, USA. We analyzed a sample of isolates received during 2012–2015 and cross-referenced cases with the Minnesota Department of Health Sexually Transmitted Disease Database to ascertain patients’ HIV status and recent chlamydia, gonorrhea, and syphilis infections. Of 691 Shigella isolates, 46 (7%) were DSA-Shigella; 91% of DSA-Shigella patients were men, of whom 60% were living with HIV. Among men, those with DSA-Shigella infection had greater odds of living with HIV, identifying as MSM, or having a recent diagnosis of a sexually transmitted disease. DSA-Shigella was associated with MSM, HIV infection, and recent sexually transmitted disease. To decrease spread of DSA-Shigella, interventions targeted at communities at high risk are needed.